Registros del ibis pico de hoz, Plegadis falcinellus (Linnaeus 1776) (Pelecaniformes: Threskiornithidae) en Colombia (2015)
In Colombia the Glossy Ibis (Plegadis falcinellus) has few records above 2000 m.a.s.l. We present a record of Glossy Ibis in the Fúquene Lagoon, Cundinamarca, Colombia, at 2600 m.a.s.l. which represents the first sighting of this bird in this wetland.